A case study of total productive maintenance implemantation in an aircraft maintenance company - KALENDER, ZEYNEP TUĞÇE (My University, 2013)
Total productive maintenance was introduced to USA in the late 1980s as a companywide strategy to increase the effectiveness of production environment. In recent years, many companies have attempted to implement this strategy to maximize equipment’s effectiveness and productivity, and minimize machine losses. In this study, main concern is how a aircraft maintenance company can apply TPM, in an efficient way. In case study we determined the steps of the maintenance proscess and then analyzed tools efficiency with using overall equipment efficiency. Needed information is gathered from calibration standars which are determined by the manufacturers of the company.
Keywords: Total productive maintenance; overall equipment efficiency; maintenance repair overhaul; aircraft maintenance; calibration